Assessment of Quality of Life in Cancer Children - Mira Irmawati; Irwanto Irwanto; Andy Cahyadi (Universitas Airlangga, 2012)
Introduction: The survival rate of cancer children has increased over the past decade. The assessment of quality of life in childhood cancer survivors is required for understanding children's psychosocial functioning, perception of illness and its effect on daily life. The objective of this study was to assess the quality of life of cancer children.Method: This study was a cross sectional study done to both parents and cancer children 5–18 years old in January-February 2012. Subject and their parents were given the PedsQL 3.0 Cancer Module that was translated in to Indonesia Language. Cronbach's alpha and Pair-t tests were used for analysis.Result: Forty-four cancer children participated, mean age 6.4 years old, 30 (56.6%) were female, 24 (45.3%) suffered from leukemia. No signiﬁcant gender differences were found for all subscales. All subscales showed satisfactory reliability (Cronbach's alpha = 0.615–0.929). The scores from children-report was higher than parents-report for treatment anxiety, cognitive problem and total scale (p<0.05), the overall scores of 61–81. The subscale procedure anxiety, worry, and pain-hurt had low-scores for both children and parent.Disscussion: PedsQL 3.0 Cancer Module is an objective instrument for measuring quality of life in cancer children and their family.